The Irish Longitudinal Study on Ageing (TILDA), 2009-2011 - Kenny, Rose Anne ([Verlag nicht ermittelbar], 2014)
The Irish Longitudinal Study on Ageing (TILDA) is a major inter-institutional initiative led by Trinity College Dublin which aims to produce a massive improvement in the quantity and quality of data, research and information relating to older people and ageing in Ireland. Eligible respondents for this study include individuals aged 50 and over and their spouses or partners of any age. The study involves interviews on a two yearly basis with a sample cohort of 8,504 people aged 50 and over (or their spouses/partners) and resident in Ireland, collecting detailed information on all aspects of their lives, including the economic (pensions, employment, living standards), health (physical, mental, service needs and usage) and social aspects (contact with friends and kin, formal and informal care, social participation). Both survey interviews and physical and biological measurements are utilized. Demographic and background variables include age, sex, marital status, household composition, education, and employment.